Vegetetive bud-burst variability of European elms - Santini, A.=700 1 Ghelardini, L.; Falusi, M.; Bohnens, J.; Buron, M.; Collin, E.; Solla, A.; Vanden, B.A.
(Es, En)
ilus., 41 ref.
Keywords: ULMUS; ULMUS GLABRA; ULMUS LAEVIS; TEMPERATURA; FRIO; ESPAÑA; GRASOS DIA; REQUERIMIENTO DE FRIO